Marge in charge - Fisher, Isla, 1976- (Fisher, Isla, 1976- Marge, 2017)
"Meet Marge, the mischievous babysitter with rainbow hair who loves to make a mess and bend the rules ... At dinnertime Chef Marge cooks up chocolate soup, and at school Marge the Musician conducts a chaotic concert in the playground! In these three stories, Jake and Jemima have brilliant fun with their new babysitter, but will they manage to tick off all the jobs on Mummy's list?